ONE-STATE SOLUTION IN RESOLVING THE ISRAEL-PALESTINE CONFLICT THE PROBLEM OF BI-NATIONAL STATE FOR ISRAEL AND PALESTINE - Veda Darari Hanifati (HI 16 UMY 180, 2016)
The One-State Solution appeared firstly in 1999 with the article written by Edward Said. Using the concept of bi-national state model of solution, this solution has becoming a known alternative to the two states solution model. The thesis aims to discover the problem of the one state solution, the bi-national state model, which hinder this model of solution to be implemented in resolving the conflict. The data collected in this thesis are secondary data obtained from books, book sections, journal article, news item, website, and document from website. The thesis shows that the one state solution faces internal and external obstacles. The solution model is greatly concerned with identity issue and historical pattern. The internal obstacles are the strong group identity, the lack of uniting characteristics, and history of hostility. The external obstacle is the two states model oriented peace process.